Pengaruh Country Of Origin, Event Sponsorship dan Citra Merek terhadap Keputusan Pembelian - Mariatuz Zakia (Journal of Economic, Management and Entrepreneurship, 2023)
The purpose of this research is to analyze and determine the influence of Country of Origin, Event Sponsorship and Brand Image on Purchasing Decisions. The type of research used in this research is multiple linear regression, assisted by processing with the SPSS (statistical package for social sciences) version 22 program so that primary data is obtained. The population in this study were Samsung smartphone users at Yudharta Pasuruan University. The sampling technique was carried out by collecting data from researchers using a questionnaire. There are three independent variables in this research, namely Country of Origin, Event Sponsorship and Brand Image. Meanwhile, the dependent variable in this research is Purchase Decision. The results of this study show that partially the country of origin has a positive and insignificant effect. However, country of origin is a variable that indirectly has little influence on purchasing decisions. Event sponsorship has a negative and insignificant effect, meaning that event sponsorship is a variable that does not have a significant direct influence on purchasing decisions. Brand image has a positive and significant effect, meaning that brand image is a variable that indirectly has a lot of influence on purchasing decisions because the higher the image of a brand can influence purchasing decisions. Simultaneously, the three variables, namely Country of Origin, Event Sponsorship and Brand Image, have a positive and significant effect on purchasing decisions.